Economic Study of Design Engineering Analysis Pipeline and SPM Study from Survey Data Meteorology and Oceanography at Unit VI Balongan - Soesanto, Edy (Greenation Publisher & Yayasan Global Resarch National, 2023)
The offshore facilities to be developed include a submarine pipeline (SPL) along with a Single Point Mooring (SPM) System located in the waters around the RU-VI Balongan special port consisting of a Single Point Mooring System (Buoy, hawser, floating hose, underbuoy, chain , anchor, PLEM etc.) which are used for loading and unloading of 2 (two) products, with coordinate location plans of 06o 15' 51.52'' S and 108o 25' 13.04'' E. and two parallel onshore pipeline lines along approximately 2.5 km (from the RU-VI refinery boundary to landfall), followed by 2 (two) parallel submarine pipeline lines of approximately 11 km (from landfall to the SPM location). With the general scope of survey work consisting of: 1) Carrying out preparations, including obtaining survey permits; 2) Building a network of control points to support topographical survey work; 3) Conducting bathymetric surveys, subbottom profiling, sonar and magnetic side scans covering the marine pipeline corridor and the SPM area; 4) Carry out meteorological and oceanographic research (met-ocean) consisting of wind observations, air temperature observations, air humidity, tide observations, current observations, sea water temperature and salinity measurements; 5) Soil investigations at sea and on land; 6) Pipe routing; and 7) Data processing and preparation of reports on survey results. In this study, we focus more on the use of meteorological and oceanographic (met-ocean) data in studying economic analysis in the engineering design plans for the Pipeline Study and SPM.